PENGARUH PENGAWASAN DEWAN, PEMAHAMAN PERATURAN DAN UNDANG â€“ UNDANG TERHADAP PENGELOLAAN KEUANGAN DAERAH DENGAN GOOD GOVERNMENT GOVERNANCE SEBAGAI VARIABEL INTERVENING - Sunartin, sunartin; wawo, andi basru; husin, husin (JPEP (Jurnal Progres Ekonomi Pembangunan), 2016)
The Effect of Board Supervision of Rules and Laws Understanding on the Managementof Local Finance with Good Government Governance as an Intervening Variable (A Study ofSKPD in South Konawe Regency).â€Supervised by Andi Basru Wawo, as Supervisor I, andHusin, as Supervisor II.This study aimed to analyze the effect of board supervision and understanding of rulesand laws on the management of local finance with good government governance as anintervening variable. The study was a causal research and the objects of the study were 31SKPD in South Konawe regency. Data were collected using a questionnaire. The data wereanalyzed using a technique of path analysis on the SPSS version 20.Result of partial analysis showed that board supervision had a positively significanteffect on good government governance, understanding of rules and laws had a positivelysignificant effect on good government governance,board supervision had a positivelysignificant effect on the management of local finance, understanding of rules and laws had apositively insignificant effect on the management of local finance, good governmentgovernance could act as an intervening variable in the relationship between boardsupervision, understanding of rules and laws, and the management of local finance.Keywords: Board Supervision, Understanding Of Rules And Laws, GoodGovernmentgovernance, The Management Of Local Finance